Survey and management of potato pests in Uganda - Cortada, L.; Coyne, D.; Nakato, V.; Kisitu, J.; Wasukira, A.; Okonya, J. (International Institute of Tropical Agriculture, 2019)
Potato (Solanum tuberosum L.) is an important food and income generating crop for its growers. The crop is also nutritionally rich in carbohydrates, vitamins (C and B), proteins, minerals (potassium) among other nutritional components. In Uganda, potato has been recognized as a crop with potential for nutrition security and income generation. Despite these benefits, average potato yield (4.8 t/ha) in Uganda is still comparatively lower than attainable global average yield (30 to 40 t/ha), owing to several biotic and abiotic production constraints. A study was conducted to establish the status of potato pests and diseases in north eastern and south western Uganda to include districts such as Mbale, Namisindwa, Kween, Kapchorwa and Kabale, Rubanda, Kisoro, respectively. The study was aimed at assessing the incidence and prevalence of key pests and diseases affecting potato in Uganda, with special emphasis on potato cyst nematode. Several pests and diseases including leaf miner flies, aphids, potato tuber moths, whiteflies, viruses, several nematode species, bacterial wilt (Ralstonia solanacaerum), and Fusarium spp. were observed to be affecting potato. Through the prospections conducted in this survey, the potato cyst nematode (Globodera rostochiensis) was identified in north eastern and south western areas of Uganda. Male farmers were more engaged in decision-making activities for potato production than their female counterparts in Eastern Uganda. An inclusive and multi institutional team was tasked to conduct this potato disease survey; this exercise was led by the International Institute of Tropical Agriculture (IITA) and the International Fertilizer Development Centre (IFDC-GIZ), with the special cooperation of the International Potato Centre (CIP), and the active engagement of the BugiZARDI-NARO and the District Production Office of the District Local Governments and Ministry of Agriculture, Animal Industry and Fisheries-Department of National Crop Certification Services.